How marriages influence early child birth registration and affect opportunities for children: a case study of Nkulumane district, Bulawayo - Nyoni, Blessing Usher (Midlands State University, 2018)
This study is an investigation on how marriages can influence early child birth registration and hamper opportunities for children. The study looks at the 4 types of marriages in Zimbabwe and how they can work for and against early child birth registration.The four types of marriages are Civil marriage 5:11, Registered customary marriage 5:07, unregistered customary marriage and cohabitation. The study compares registered marriages versus the unregistered customary marriages on birth registration. The main mission of this dissertation is to analyse why people fail to comply to early child birth registration rules , to scrutinise why they fail to register children as per the Birth and Death registration rules and regulations. The project also seeks to view birth registration from a wide spectrum of analysis tracing the hindrances and obstacles that communities face in Nkulumane District of Bulawayo leading to failure to early child birth registration. The research takes a closer look on marriages and the most dominant marriage in society which is unregistered customary. The study also noted that the right of children are violated due to lack of birth certifcates. It also toured the other contributory factors to lack of early child birth registration which were classified into economic,social,political,religious and individual reasons which contribute to lack of early child birth registration.A birth certificate is an important document that has got the capacity to promote poverty in the lives of children through denying them access to opportunities that needs the birth certificate.In the contemporary world characterised by migration absorption of states into the global world a birth certificate is now a basic document for children.